The Legal Protection For Children Of Sexual Violence Victims In Indragirii Hilir Regency - Wahyuni, Fitri; Irawan, Aris; Rahmah, Siti (CV. Inara, 2021)
Currently, the phenomenon of children sexual abuse is a crime that is very distressing to society. It shows that children sexual abuse is an iceberg phenomenon that must be prevented so that children are no longer victims of sexual harassment by the responsible party. This research used normative legal as research methods. The data sources in the form of secondary data including primary, secondary and tertiary legal materials. Meanwhile, the data analysis used is in the form of qualitative analysis and deductive conclusion. From the results of this research, it was concluded that the protection efforts had been made through the regulation of laws and penal efforts both in the Criminal Code and the children protecting laws by providing criminal sanctions for sexual offenders. However, these efforts were not sufficient and they must be carried out through non-penal efforts by providing sex education from an early age and teaching religious values.